Methods for use of insectides in stored wheat - Fehn, Licelma Martins (Pesquisa Agropecuaria Brasileira, 2014)
As part of the complex problem of wheat production the present study was focused on methods protecting the stored grain from insect attack. Ignorance of the technique of applying protective measures to stored grains has been cited as the cause of production losses. Lack of knowledge has further repercussions in that it increases the possibility of toxic residues reaching humam consumers. The problem exists in Brazil due to the increase in number and specifity of insecticides available for use in wheat destined for seed or consumption. For this reason numerous foreign and domestic reports were reviewed, seeking improved methods of combating infestation under our storage conditions. A comparison of the storage systems used in Brazil during the last few years was made with those in four other countries, Australia, Canada, Great Britain and the United States. The advantages of using insecticides based on phosphorus of aluminum, "Phostoxin" and "Delicia" over methyl bromide and carbon bisulfide were evaluated, considering ease of application. For wheat destined for human consumption the advantage of employing products with a base of "Puretron", malathion, and carbamate were compared with those of DDT and BHC. Insects considered to be limiting factors in the storage of wheat were investigated. Those meriting attention were the weevils, Sitophilus oryzae (Linn., 1763) and the moth Sitotroga cerealella (Oliv., 1819). Each is responsible for loss of value in stored wheat. The moisture content of wheat is the most important factor in the use of fumigants. This is especially so for methyl bromide. In the presence of high moisture this gas has the ability to provoke germination. With this fact as a basis the dosages of the gases and the time of exposure were explored and initial data established for wheat as the basis of the experiment. Experiments on the use of gas, in hermatically sealed chambers and under waterproof tarps; the use of powered insecticides, acting on contact or ingestion such as DDT and BHC; insecticides based on malathion; the vegetable derivatives pyrethrum with its synergistic ester pyrethrin that acts on contact and does not affect man were included. In latter experiment the carbonates were introduced in the insecticide Carbaryl. These also have a low toxicity for man. The results obtained were based on a survey of the following data: a) Effect of germination, b) Loss of weight in stored wheat, c) Live-dead weevil counts, d) Number of damaged grains. As wheat to be used as seed should not be treated with insecticides that affect germination and wheat to be used as food must not have residue toxic to warm blooded animals, the results tabulated indicate the correct insecticide for each use. Giving the dosage of the fumigants, establishing the moisture limits for employing methyl bromide and carbon bisulfide and the limits to which gases based on aluminum phosphate may be used. Regarding the use of powered insecticides it was concluded that for grain to be used for human consumption it would be advantageous to use "Pirisa Protetor de Grãos", a national product with a carbamide and malathion base. The use of BHC and DDT mists as protection is permited in more general cases. The studies on liquid insecticides such as malathion, piretrin and wetable carbamates are reported. The presentation ends with a suggested series of norms to be followed in the fumigation and storage of wheat.